2023
DOI: 10.1002/jcb.30377
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuins and their influence on autophagy

Abstract: Sirtuins and autophagy are well‐characterized agents that can promote longevity and protect individual organisms from age‐associated diseases like neurodegenerative disorders. In recent years, more and more data has been obtained that discerned potential overlaps and crosstalk between Sirtuin proteins and autophagic activity. This review aims to summarize the advances within the field for each individual Sirtuin in mammalian systems. In brief, most Sirtuins have been implicated in promoting autophagy, with Sir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 109 publications
0
13
0
Order By: Relevance
“…Autophagy is regulated by PTMs such as acetylation ( Xu and Wan, 2022 ), and SIRT1 is a representative deacetylase that profoundly involved in the regulation of autophagy ( Baeken, 2023 ). Previous studies have revealed that SIRT1 modulates autophagy at transcriptional level via deacetylating Forkhead Box O1 (FOXO1) and Forkhead Box O3 (FOXO3) ( Hariharan et al, 2010 ; Dusabimana et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy is regulated by PTMs such as acetylation ( Xu and Wan, 2022 ), and SIRT1 is a representative deacetylase that profoundly involved in the regulation of autophagy ( Baeken, 2023 ). Previous studies have revealed that SIRT1 modulates autophagy at transcriptional level via deacetylating Forkhead Box O1 (FOXO1) and Forkhead Box O3 (FOXO3) ( Hariharan et al, 2010 ; Dusabimana et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sirtuin 1 (SIRT1), a longevity factor, is a well-studied deacetylase that removes acetyl group from the lysine residue from acetylated proteins ( Yang et al, 2022 ). Previous studies have found that SIRT1 functions as a crucial regulator at different stages of autophagy and activation of SIRT1 promoted autophagy ( Baeken, 2023 ). In addition, treatment with SIRT1 activator has been suggested as an effective approach to alleviate inflammatory injury ( Yang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…60 SIRT1 is a nicotinamide adenine dinucleotide-dependent histone deacetylase, promote longevity and protect individual organisms from age-associated diseases. 61 In additional, sphingosine 1-phosphate (S1P) alleviates radiation-induced ferroptosis in ovarian granulosa cells by upregulating GPX4. Physical activity activates the SIRT1 pathway, 62 which has also been linked to creativity.…”
Section: Regulating Gpx4 Pathway In Ferroptosismentioning
confidence: 99%
“…In compromised neurons, autophagy vacuoles containing AB pack into large structures forming flower-like perikaryal rosettes known as PANTHOS (poisonous Anthos or flower) which occur in the brains of AD patients ( Lee et al, 2022 ). Another key player in autolysosome acidification is SIRT5, a sirtuin protein found in the mitochondria ( Baeken, 2023 ). SIRT5 mediates the deacetylation and activation of the enzyme lactate dehydrogenase B found on the lysosomal membrane supplying the lysosomes with protons for lysosomal acidification ( Baeken, 2023 ).…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…Another key player in autolysosome acidification is SIRT5, a sirtuin protein found in the mitochondria ( Baeken, 2023 ). SIRT5 mediates the deacetylation and activation of the enzyme lactate dehydrogenase B found on the lysosomal membrane supplying the lysosomes with protons for lysosomal acidification ( Baeken, 2023 ). Due to both its role in lysosomal acidification and its decreased expression in AD, SIRT5 has been regarded as an attractive autophagy-related target in AD therapeutics ( Baeken, 2023 ).…”
Section: Alzheimer’s Diseasementioning
confidence: 99%